The contribution of mental rigidity to the level of performance of the Premier League football referees - Satar, Khaleel; Ismaeel, Huida; Thari, Ahmed (Journal of Physical Education, 2018)
The contribution of mental rigidity to the level of performance of the Premier League football refereesThe attention to the referees of football comes from their basic importance in the game and the extent of their contribution to the enjoyment and safety of players and the achievement of justice as the attention of the concerned football and the process of follow-up analysis and study the behavior of the referees in order to qualify them according to scientific curricula accurate and comprehensive and prepare correctly true to their position in the leadership of the game and access To safety as few mistakes as possible, to control and overcome stress as well as to control the emotional emotions that affect his decisions and his mental and physical responses fast.The referees come under difficult tasks that require referees to have individual characteristics. The referees face a large number of different game situations and many interceptions in games. These situations are renewed from one game to the next, so they must not be influenced by them and make the right decisions. Attitudes, and The level of referee performance is affected by individual differences and the ability to use memory and previous experiences, which can be useful in finding the most appropriate solution in situations and get rid of the problem and find the best solutions.It is important that the referees are subjected to great pressure and difficult positions, both in the same game as a result of objections by the players or the technical area or the masses present in the game so researchers have studied the rigidity mental mental rigidity of the rulers of the Premier League football and its contribution to the level of performance of the rulers to be A step in achieving the evolution of rulers and raise their levels in the future.